2022
DOI: 10.1177/03635465221120385
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Bone Microarchitecture at Distal Radial and Tibial Reference Locations Is Not Related to Injury Site in Athletes With Bone Stress Injury

Abstract: Background: Bone stress injuries (BSIs) are common sports injuries that occur because of an imbalance between microdamage accumulation and removal through bone remodeling. The underlying bone phenotype has been assumed to be a contributing factor. However, the bone microarchitecture of athletes with BSI is not well characterized, and no study has investigated whether impaired bone microarchitecture is associated with bone composition or anatomic site of injury. Purpose/Hypothesis: This cross-sectional study ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…A study from Nattiv et al 97 indicated longer time to RTS after BSIs at trabecular-rich bone sites compared with cortical-rich sites, but this classification by bone composition ratio remains to be established histologically. As such, it was presumed that bone composition may influence RTS, but evidence is inconclusive 5 99…”
Section: Discussionmentioning
confidence: 99%
“…A study from Nattiv et al 97 indicated longer time to RTS after BSIs at trabecular-rich bone sites compared with cortical-rich sites, but this classification by bone composition ratio remains to be established histologically. As such, it was presumed that bone composition may influence RTS, but evidence is inconclusive 5 99…”
Section: Discussionmentioning
confidence: 99%